Co-constructed competencies of facilitators supporting Newly Qualified Professional Nurses to meet the outcomes of a Person-centered Nurse Residency Programme - Coetzee, Isabel M. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.